Technology-Based Education Transformation: Futuristic, Quality, Resilient, and Sustainable Education System in the Age of Society 5.0 - Sihombing, Adison Adrianus; Putranti, Honorata Ratnawati Dwi; Noviani, Nur Laili; Atasoge, Anselmus Dore Woho (Universitas Pendidikan Ganesha, 2024)
The transformation of digital education in Indonesia has not been seen as a need for future education services towards society 5.0. This study aims to describe, explore and analyze that technology-based education is an urgent new model in organizing the education system. This qualitative study is based on secondary data from literature studies. The research findings are that the integration of digital technology in education is an inevitable reality to build a quality-sustainable education paradigm. This integration is done through the process of transforming educational services from the classroom into a multifaceted digital platform that includes online learning, virtual classrooms, and e-books. This transformation is a consequence of the development of society towards society 5.0; the prevalence of the digital-native generation and global disruptions such as pandemics and environmental crises. Thus, the current social reality requires an adaptive-innovative education system and collaboration among stakeholders. This collaboration ensures the realization of an education system that is aligned with the complexities of the current and future socio-technological landscape, ultimately promoting inclusivity, resilience, and sustainability.